Preparation and characterization of phytosterol-loaded microcapsules based on the complex coacervation. (December 2021) - Li, Feifan; Wang, Hongfu; Mei, Xiaohong
Abstract: The study developed the microcapsules by complex coacervation with soybean protein isolate (SPI) and pectin to be used for phytosterol (PS) encapsulation. Fluorescence analysis suggested the formation of SPI/pectin complex coacervates. Fourier-transform infrared further confirmed the electrostatic attraction between SPI and pectin. X-ray diffraction and differential scanning calorimetry analysis revealed that pectin molecule chains were closely absorbed by SPI molecules during coacervation. PS was dispersed into conjugated linoleic acid and used as the core materials of the microcapsules. The microcapsules that were made at pH 2.5 with SPI/pectin mixing ratio of 5:1 exhibited the highest encapsulation efficiency of PS. Confocal laser scanning microscopy image presented that the oil droplets were encapsulated by SPI/pectin coacervates. Scanning electron microscopy images showed the microcapsules with a rough and irregular shape and no obvious cracks or slits on the surface. Meanwhile, core materials showed favorable oxidation stability and gastric stability after encapsulation. However, after 7 h digestion in simulated intestinal fluid, about 70% of the encapsulated PS was released in sustained release mode. These results could be useful for designing an ideal carrier to deliver PS by complex coacervation using protein and polysaccharides. Graphical abstract: Image 1 Highlights: Pectin was capable of absorbing onto the surface of soy isolate protein via electrostatic interaction to form microcapsule. The microcapsule exhibited a favorable encapsulation efficiency of PS. The microcapsules showed a sustained release of phytosterol in stimulated intestinal fluid.